Generation of relativistic vortex laser beams by spiral shaped plasma - Tianyun Long; Cangtao Zhou; Libao Ju; Taiwu Huang; Mingyang Yu; Ke Jiang; Chaoneng Wu; Sizhong Wu; Hua Zhang; Bin Qiao; Shuangchen Ruan; Xiantu He (Physical Review Research, 2020)
Three-dimensional particle-in-cell simulations show that relativistic Gaussian laser light can be transformed into relativistic vortex laser light with axial orbital angular momentum (OAM) as it propagates through a homogeneous spiral-profiled low-density plasma slab. In the process, the plane equiphase surfaces of the Gaussian laser undergo azimuthal modulation and become a continuous helical surface. The intensity profile of the laser changes from maximum-on-axis to donut-shaped. Because of the azimuthally varying slab thickness, the laser ponderomotive and the charge-separation forces exert a torque on the plasma when it passes through it, resulting in the creation of oppositely directed OAM in the plasma ions and the laser light, with the electrons remaining nearly OAM free. The proposed scheme can be used to generate both single- and multi-mode relativistic vortex lasers propagating along the direction of the input laser, which is especially convenient for many applications.